Water resistance of magnesium oxychloride cement wood board with the incorporation of supplementary cementitious materials. (20th September 2020) - He, Pingping; Poon, Chi Sun; Tsang, Daniel C.W.
Highlights: New chemical bands such as carboxylate were detected and a new phase (dashkovaite) was observed in the wood-MOC paste. The wood fibre cement mortar showed lower expansion compared to pure MOC paste after water immersion. The wood cement pastes prepared with the longer fibres had higher volume stability in air curing. Abstract: The water resistance of magnesium oxychloride cement (MOC) prepared with supplementary cementitious materials (SCMs), pulverized fuel ash (PFA), glass powder (GP), incinerated sewage sludge ash (ISSA), and wood fibre obtained from waste timber formworks and subjected to CO2 curing was analysed. The timber formworks were crushed and sieved to different lengths of wood fibre: Fine (0–0.6 mm), Medium (0.6–2.36 mm), Coarse (2.36–5 mm), and a mixture of the above (Mixed) without sieving. The flexural strength and volume stability of wood-cement pastes before and after water immersion were tested. Flexural strength retention was used to evaluate the water resistance of the wood cement paste. It was found that wood fibre could enhance the volume stability of MOC paste matrix after 28 days of water immersion due to the high porosity that accommodated the expansion of MOC paste. Attenuated total reflectance-Fourier transformed infrared spectroscopy (ATR-FTIR) showed new bands were formed with the incorporation of wood fibre. X-ray diffraction (XRD) results showed the formation of dashkovaite (Mg(HCOO)2 ·2H2 O) in the wood-MOC paste. The flexural strength of the wood-cement paste increased with the increasing fibre length. Adding supplementary cementitious materials, especially incineration sewage sludge ash (ISSA), could improve the water resistance and volume stability of the wood-cement paste.